2005
DOI: 10.1179/037366805x52988
|View full text |Cite
|
Sign up to set email alerts
|

Ephemerum hibernicumsp. nov. (Bryopsida: Ephemeraceae) from Ireland

Abstract: Ephemerum hibernicum sp. nov. is described from inundation zones of two lakes and a river in north-central Ireland and a river in western Ireland. It is most similar to E. crassinervium and E. sessile, but differs from both of these in several characters of the leaves. In particular, papillae on the upper lamina are much lower than in most E. crassinervium, while the leaves are longer and wider than in E. sessile, with a wider lamina towards the leaf apex, less well-defined costa and sometimes with large spino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…hibernicum' are mainly distinct from those of E. sessile, but some individual plants are difficult to place on the basis of leaf characters. Indeed, there are few consistent differences between E. rutheanum and E. sessile other than the more strongly toothed leaves and better developed lamina in the leaf apex of the former taxon (Tables 1 and 2; Holyoak & Bryan, 2005). Differences between the tubers of E. rutheanum (as 'E.…”
Section: C) Plants Intermediate Between E Sessile and E Rutheanummentioning
confidence: 91%
See 2 more Smart Citations
“…hibernicum' are mainly distinct from those of E. sessile, but some individual plants are difficult to place on the basis of leaf characters. Indeed, there are few consistent differences between E. rutheanum and E. sessile other than the more strongly toothed leaves and better developed lamina in the leaf apex of the former taxon (Tables 1 and 2; Holyoak & Bryan, 2005). Differences between the tubers of E. rutheanum (as 'E.…”
Section: C) Plants Intermediate Between E Sessile and E Rutheanummentioning
confidence: 91%
“…Comparative studies have established that the same taxon was described by Holyoak & Bryan (2005) as E. hibernicum, a supposed new species from Ireland. There are no significant differences between them, so E. hibernicum is regarded as a synonym (see below).…”
Section: E Serratum Var Praecox Awhwalther and Molendomentioning
confidence: 94%
See 1 more Smart Citation
“…Holyoak & V.S. Bryan (Hill et al, 1994;Holyoak, 2001;Holyoak & Bryan, 2005), the liverworts Riccia canaliculata Hoffm., R. cavernosa Hoffm. and R. huebeneriana Lindenb.…”
Section: Descriptionmentioning
confidence: 96%
“…It is unsurprising therefore that the first detailed systematic survey of reservoirs in Ireland (Holyoak, 2001;Holyoak & Bryan, 2005) yielded two new species of Ephemerum and numerous new records for these reservoir specialists. More remarkably, in a similar detailed survey of reservoir bryophytes in northern England, Hodgetts (2003) reported that much of the Physcomitrium-like material growing at Lindley Wood Reservoir in 2001 and 2003 appeared to be a hybrid between P. sphaericum and Aphanoregma patens.…”
Section: Descriptionmentioning
confidence: 97%